The Role of Caspases in Inflammatory Responses against Gram Negative Infections - Hussein Alwan, Ali; Ibrahim Khadhim, Noor; Zuhair Azeez, Areej (International Journal of Psychosocial Rehabilitation, 2020)
Pseudomonas aeruginosa has emerged as one of the most difficult nosocomial pathogens. The present study aims to estimate the role of caspases in inflammatory responses against Pseudomonas aeruginosa infection. This study was performed on 50 isolates from infected patients. The diagnosis isolates depending on the macroscopic, microscopic, biochemical, and API20E tests. Results show that the percentage of isolates according to clinical sources were (38%) from burns, (24%) from urine, (6%) from ear swabs, (20%) from sputum, and (12%) from wounds. Different abilities to resist antibiotics included amoxicillin-clavulanic acid, trimethoprim-sulfamethoxazole, and erythromycin, which are effective against P. aeruginosa. The ability of biofilm formation as a virulence factor by the microtiter plate method (MTP) resulted in the revelation that 92% of P. aeruginosa have the ability to form biofilm. Molecular diagnosis of isolates implemented by the 16SrDNA gene, in addition to detecting the virulence gene (Flic gene), showed that 90% of isolates were positive. The results of the CASP-1 patients sequencing showed 70% have heterozygous nucleotides, and the level of IL-1β showed no significant differences between infected and non-infected individuals. Comparison between IL-1β level and patients age group, where the F, G, and H groups revealed a significant difference. The comparison between sources of infection recorded higher significant differences between cystic fibrosis compared with wound and UTI sources.